The Influence of Family Psychoeducation on Family Knowledge, Ability and Burden in the Care of People with Schizophrenia at the Psychiatric Polyclinic of Pariaman Hospital - Hendro, Yuli; Putri, Dewi Eka; Renidayati (GoAcademica Research & Publishing, 2024)
This study aims to determine the influence of family psychoeducation on knowledge, abilities and family burden in caring for people with Schizophrenia at the Psychiatric Polyclinic at Pariaman Regional Hospital. This research was carried out at Pariaman Hospital from September 2022 to September 2023. This type of research is quantitative and quasi-experimental with a control group. The population in this study were families of ODS who visited the mental health clinic at Pariaman Regional Hospital, totalling 94 people and a sample of 32 people. The data collection tool/instrument used was a questionnaire. Data analysis in this research uses the Validity Test, Reliability Test, Univariate Analysis and Bivariate Analysis. The results of this study show that family psychoeducation therapy has a positive impact on increasing the knowledge and abilities of families who care for family members with Schizophrenia. A comparison between families who received Psychoeducational therapy and those who did not showed significant differences in knowledge, abilities and family burden. Family Psychoeducational Therapy can be considered an effective intervention in supporting families who care for family members with Schizophrenia in the psychiatric polyclinic of Pariaman Hospital.